Integrated Aerodynamic-Ballistic Performance Analysis of Morphing Missiles with Deformed Cross-sections - Zhang, Ziyang; Wang, Xugang; Chen, Jinquan (Journal of physics. Conference series, 2024)
To analyze the impact of various cross-sectional shapes and tailfin configurations on the flight performance of morphing missiles, an integrated aerodynamic and ballistic performance analysis was conducted on gliding extended-range missiles as the primary research subject. Utilizing an engineering algorithm, we calculated the lift-drag characteristics across different cross-sectional shapes and tailfin configurations, identifying the ellipticity ratio as the pivotal parameter influencing the missile’s lift-drag ratio, which correlates positively with overall performance. Configurations with greater ellipticity ratios demonstrate a lift-to-drag ratio advantage in the subsonic speed range, which can counteract the performance losses post-transonic range and improve the missile’s aerodynamic capabilities. The “+”shaped tailfin configuration demonstrated a lift-to-drag ratio advantage at all test speeds and showed no performance inconsistencies between speed ranges. Ballistic simulations indicate that configurations with ellipticity ratios of 1.25 and 1.50 achieve range increases of 8.9% and 19.5%, respectively, over the standard circular cross-section. Ellipticity ratio has a positive correlation with the maximum range, and the growth rate of this range slightly increases with greater ellipticity. The research findings elucidate how cross-sectional deformation contributes to the enhancement of missile performance and offer technical guidance for the design of related projects.